2022
DOI: 10.1001/jamainternmed.2021.7344
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Changing Estimated Glomerular Filtration Rate Thresholds in Older Persons

Abstract: 2. O'Hare AM, Rodriguez RA, Rule AD. Overdiagnosis of chronic kidney disease in older adults-an inconvenient truth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…The grouping of the fourth physical examination results was performed according to age (the subjects in this physical examination were all older than 30 years); the prevalence of CKD in the 30-39-year age group was 12.0%, the prevalence of CKD in the 40-49-year age group was 9.8%, and no one in the over 50 age group had CKD. Since age is a known risk factor for CKD, previous studies have also shown that the overall prevalence of CKD increases with age [4], but the results of this study showed that the prevalence of CKD decreased with increasing age and that the incidence rate in the 30-39-year age group (12.0%) was the highest. A possible reason for this finding is that the subjects in this study are aircrew members, and thus, if they have a medical condition, they cannot continue to serve in the Air Force; in this study, early-stage CKD (stages 1 and 2) is dominant, and the GFR is still within the normal range; however, to diagnose early-stage CKD, renal parenchymal damage is required (at least one item of urine protein, urine RBC positivity, or urine pH > 8), thus reducing the explanatory power of age on the risk of early-stage CKD.…”
Section: Comparison Of Ckd and The Number Of Abnormal Predictorscontrasting
confidence: 81%
See 1 more Smart Citation
“…The grouping of the fourth physical examination results was performed according to age (the subjects in this physical examination were all older than 30 years); the prevalence of CKD in the 30-39-year age group was 12.0%, the prevalence of CKD in the 40-49-year age group was 9.8%, and no one in the over 50 age group had CKD. Since age is a known risk factor for CKD, previous studies have also shown that the overall prevalence of CKD increases with age [4], but the results of this study showed that the prevalence of CKD decreased with increasing age and that the incidence rate in the 30-39-year age group (12.0%) was the highest. A possible reason for this finding is that the subjects in this study are aircrew members, and thus, if they have a medical condition, they cannot continue to serve in the Air Force; in this study, early-stage CKD (stages 1 and 2) is dominant, and the GFR is still within the normal range; however, to diagnose early-stage CKD, renal parenchymal damage is required (at least one item of urine protein, urine RBC positivity, or urine pH > 8), thus reducing the explanatory power of age on the risk of early-stage CKD.…”
Section: Comparison Of Ckd and The Number Of Abnormal Predictorscontrasting
confidence: 81%
“…Spearman correlation coefficient: the relationships between risk factors and renal function were analysed. 4.…”
mentioning
confidence: 99%
“…In this regard, another relevant point is the current debate about the suggested agedependent CKD definition. Nephrologists are still arguing whether isolated mild eGFR reductions to a level just below 60 ml/min/1.73 m 2 should even be considered a disease in older adults (Delanaye et al, 2019;Cruz-Jentoft, 2022;Liu et al, 2022). Considering the effect of comorbidity and renal senescence on Frontiers in Pharmacology frontiersin.org eGFR decline (Glassock et al, 2020), many authors suggest avoiding the use of a "one-size-fits-all approach" for CKD diagnosis and to rethink CKD definition to include agespecific eGFR thresholds (Delanaye et al, 2019;Glassock et al, 2020).…”
Section: Chronic Kidney Disease Underdiagnosismentioning
confidence: 99%
“…Adapting chronic kidney disease (CKD) definition to age is a matter of debate [ 1 , 2 ]. The threshold for defining CKD stage 3a has been suggested to be changed to estimated glomerular filtration rate (eGFR) < 45 ml/min/1.73 m 2 , to account for expected changes in eGFR with normal ageing, avoid overdiagnosis and provide CKD diagnostic and classification systems that are less discriminatory toward the ever-expanding older component of the global population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%